Gα13‐mediated LATS1 down‐regulation contributes to epithelial‐mesenchymal transition in ovarian cancer. Issue 12 (28th September 2019) - Yagi, Hiroshi; Onoyama, Ichiro; Asanoma, Kazuo; Hori, Emiko; Yasunaga, Masafumi; Kodama, Keisuke; Kijima, Masako; Ohgami, Tatsuhiro; Kaneki, Eisuke; Okugawa, Kaoru; Yahata, Hideaki; Kato, Kiyoko
Abstract : Gα13, a heterotrimeric G‐protein of the Gα12/13 subfamily, is associated with aggressive phenotypes in various human cancers. However, the mechanisms by which Gα13 promotes cancer progression have not been fully elucidated. Here, we demonstrate that the activation of Ga13 induces epithelial‐mesenchymal transition in ovarian cancer (OvCa) cells through down‐regulation of large tumor suppressor kinase (LATS) 1, a critical component of the Hippo signaling pathway. A synthetic biology approach using a mutant GPCR and chimeric G‐protein revealed that Gα13 ‐regulated phosphorylation of LATS1 at serine 909 within its activation loop induced recruitment of the itchy E3 ubiquitin protein ligase to trigger LATS1 degradation. Our findings uncover novel mechanisms through which Gα13 activation induces dysregulation of the Hippo signaling pathway, which leads to aggressive cancer phenotypes, and thereby identify a potential target for preventing the metastatic spread of OvCa.—Yagi, H., Onoyama, I., Asanoma, K., Hori, E., Yasunaga, M., Kodama, K., Kijima, M., Ohgami, T., Kaneki, E., Okugawa, K., Yahata, H., Kato, K. Gα13 ‐mediated LATS1 down‐regulation contributes to epithelial‐mesenchymal transition in ovarian cancer. FASEB J. 33, 13683‐13694 (2019). www.fasebj.org